Prosocial Behavior in a Chilean School: An Intervention Based on Student’s Subjectivity - Cuadra-Martínez, David (2020)
This paper aims to describe and interpret the process of subjective change, based on an intervention aimed at the reconstruction of subjective theories of prosocial behavior, in secondary students of a subsidized private high school in Copiapó, Chile. Forty-five high school students participated in the intervention, and the effects of the intervention change were evaluated by using qualitative methodology. Episodic interviews and discussion groups were applied. Data was analysed through thematic coding. The results showed that there was a change in the structure and content of the subjective theories of students about prosocial behaviour, which was associated with greater functionality to behave prosocially. In the discussion, the subjective change produced was analysed. Likewise, the need to continue conducting studies aimed at enriching the intervention for the development of prosocial behaviour was highlighted.